CsPbBr3/CdS Core/Shell Structure Quantum Dots for Inverted Light-Emitting Diodes Application - Tang, Xiaosheng; Yang, Jie; Li, Shiqi; Chen, Weiwei; Hu, Zhiping; Qiu, Jing (Frontiers in Chemistry, 2019)
The novel CsPbBr3/CdS core/shell structure quantum dots (QDs) were successfully synthesized by a facile hot-injection method. The corresponding CsPbBr3/CdS QDs based light-emitting diodes (QLEDs) were further prepared, which demonstrated the maximum luminance of 354 cd/m2 and external quantum efficiency (EQE) of 0.4% with the current efficiency (CE) of 0.3 cd/A . Moreover, the optoelectronic performance of the CsPbBr3/CdS QDs based QLEDs exhibited comparable enhancement in contrast to the pure CsPbBr3 QDs based QLEDs. Hypothetically, the novel CsPbBr3/CdS structure QDs introduced one new route for advanced light emission applications of perovskite materials.